The Effect Of Transformational Leadership Style, Work Discipline and Motivation On Employee Performance at The Warship Division PT. Indonesian PAL (Persero) SURABAYA - Suryati Eko Putro (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to analyze the effect of transformational leadership style, work discipline and motivation on employee performance in the battleship division of PT. PAL INDONESIA (Persero) Surabaya. The study was conducted at the Warship Division of PT. PAL INDONESIA (Persero) Jalan Ujung, Surabaya. When the study was conducted in October - December 2019. This study used sampling data from 63 employees through questionnaires. The type of data used isquantitative. In this research, the resulting t test shows that the transformational leadership style variable has a partial effect on Y with a regression coefficient value of Transformational Leadership Style (X1) of 0.168, the value of the Work Discipline regression coefficient (X2) of 0.292, and the Motivation regression coefficient (X3) of .294. While the F test, obtained f count> f table is 33.016> 2.76 so that it can be concluded that the independent variables of transformational leadership style (X1), work discipline (X2), motivation (X3) have a significant influence simultaneously on the dependent variable of employee performance (Y)This research is expected to be able to support the basic decision making for the battleship division of PT. PAL INDONESIA (Persero) related to transformational leadership style (X1), work discipline (X2), motivation (X3). It aims to maintain and develop employee performance better than before. In addition, this research is expected to be able to provide new knowledge about transformational leadership style (X1), work discipline (X2), motivation (X3) in the battleship division of PT. PAL INDONESIA (Persero)Surabaya.